2011
DOI: 10.1186/1472-6750-11-70
|View full text |Cite
|
Sign up to set email alerts
|

Specific and sensitive quantitative RT-PCR of miRNAs with DNA primers

Abstract: BackgroundMicroRNAs are important regulators of gene expression at the post-transcriptional level and play an important role in many biological processes. Due to the important biological role it is of great interest to quantitatively determine their expression level in different biological settings.ResultsWe describe a PCR method for quantification of microRNAs based on a single reverse transcription reaction for all microRNAs combined with real-time PCR with two, microRNA-specific DNA primers. Primer annealin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
243
0
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 262 publications
(253 citation statements)
references
References 26 publications
3
243
0
7
Order By: Relevance
“…A tail of six bases (CTGGAC) was added to the 5= end of all primer sequences, as this improves the performance of short primers (17)(18)(19).…”
Section: Repeat the Ppr Analysismentioning
confidence: 99%
“…A tail of six bases (CTGGAC) was added to the 5= end of all primer sequences, as this improves the performance of short primers (17)(18)(19).…”
Section: Repeat the Ppr Analysismentioning
confidence: 99%
“…To quantify and validate sRNA sequencing, we did qRT-PCR [43]. Specific primers were designed for three known miRNAs, miRNA 166, 157 and 159 and two novel candidates to determine the expression.…”
Section: Qrt Pcrmentioning
confidence: 99%
“…Because it is more sensitive, easier, and less time-consuming than approaches such as cloning, northern blotting, microarray analysis, and deep sequencing, a combination of reverse transcription (RT) and quantitative PCR, or RT-qPCR, is currently the most convenient and practical means of detecting precursor and mature miRNAs. Four well-developed RT-qPCR methods of miRNA detection, each with its own advantages and disadvantages, have recently become established: stem-loop RT-qPCR, 2) poly(A)-tailing RT-PCR, 3) primer-extension RT-qPCR 4) with various improvements, [5][6][7][8][9] and miQPCR. 10) Although stem-loop RT-qPCR is the most frequently used of these methods, in previous studies we were unable to detect certain rice miRNAs using it.…”
mentioning
confidence: 99%
“…9,19) It has been suggested that to some extent the stem-loop method is more sensitive, whereas the poly(A)-tailing method is more specific. We found that both the stemloop and the poly(A)-tailing method can be used to detect highly abundant miRNAs at similar levels of accuracy and specificity (as confirmed by sequencing).…”
mentioning
confidence: 99%
See 1 more Smart Citation